[Date Index] [Thread Index] [Author Index]
Re: What's wrong with this assuming?
Try: Assuming[x^2 + x == h, Simplify[(x^2 + x)^2 + h]] Your original expression means the same thing as: FullSimplify[ Assuming[x^2 + x == h, (x^2 + x)^2+h] ] And that's clearly not what you intend, which is: Assuming[[x^2 + x == h, FullSimplify[(x^2 + x)^2 + h] ] Actually, Simplify will do nicely instead of FullSimplify here. On 7/20/2010 3:43 AM, Sam Takoy wrote: > Hi, > > > I have a situation where I have to simplify an expression that contains > x and h, but x is given implicitly by h, so I can't explicitly eliminate > it. So here's a simpler example that I'm trying and it does nothing: > > Assuming[x^2 + x == h, (x^2 + x)^2+h] // FullSimplify > > Is there a way to make this work? > > Thanks! > -- Murray Eisenberg murray at math.umass.edu Mathematics & Statistics Dept. Lederle Graduate Research Tower phone 413 549-1020 (H) University of Massachusetts 413 545-2859 (W) 710 North Pleasant Street fax 413 545-1801 Amherst, MA 01003-9305